Dissecting The Case Of Karen Agustiawan (Former President Director Of Pt. Pertamina) Through Analysis Of The Teaching Of Causality - Hadi Purnomo (Jurnal Sosial Sains dan Komunikasi, 2022)
A State-Owned Enterprise is a form of company whose capital is partly or wholly owned by the state. Therefore, when it makes a loss, law enforcement officials immediately qualify it as a criminal act of corruption. This cannot be separated from the conflict of legal norms related to the regulations governing it. Basically, it’s directors have a scope of duties to run and develop their business, which is inseparable from the possibility of losses. The aim of this research is to dissect the case of Karen Agustiawan through the teaching of causality, so that we will be able to see the facts that are factors that contribute to causing state financial losses, as well as see whether or not the burden of criminal responsibility can be assigned to the directors. This research was conducted using normative juridical research methods and a case approach. The conclusion of this research is that the teaching of causality can be applied to analyze corruption offenses, so that we can see a series of facts that constitute acts against the law as well as the intention of the perpetrators and contribute to the emergence of state financial losses. In the case of Karen Agustiawan, another factor that must be considered is the formal factor in the form of the application of the principles of Business Judgment Rules which can be an element of forgiveness that cannot be held criminally liable to the Board of Directors.